Sub-Saharan Africa and the World: History of Connections - Lvova Eleonora Sergeevna (Ученые записки Института Африки Российской академии наук)
Today, the attention of the public, businessmen, politicians, scientists is increasingly attracted to Africa, including Tropical (Sub-Saharan) Africa. However, these areas have never been isolated and always occupied a special place in the global economic and cultural ties. This paper, based on the research of a wide range of written sources of ancient, classical, and medieval periods, is devoted to the historical analysis of the relations of the peoples of Sub-Saharan Africa with the outside world. The work highlights the depth and long history of economic, cultural, and trade contacts going back several thousand years. It explores the directions of trade routes that facilitated the spread of goods, cultural ideas, and technologies, as well as the types of goods that were of particular value to participants in international trade. The author describes in detail such phenomena as the slave trade and the book trade, the money, and the exchange values that were circulating on the continent. It is known that African traders entered into transactions with merchants from China, India, the Roman Empire, Byzantium, and European countries, were involved in world trade, and had a good command of the market trends. Africa became part of the world economy many centuries ago, and this fact is evidenced by written and material sources from different parts of the world. Nevertheless, this area of African studies remains understudied, creating lacunas in understanding the pre-colonial history of the region. This article is, in a way, an appeal to contemporary Africanists to pay more attention to the study of Africa’s pre-colonial history, without knowledge of which it is often difficult to explain some current conflicts and contribute to their resolution.